PEMAPOSI: Media Interaktif untuk Meningkatkan Pemahaman Teks Eksposisi Siswa Kelas 4 : Studi kevalidan dan Kepraktisan - Nabila Nor Isnaini; Fatimah Anisalikha; Diva Mustika Utami; Muhammad Hasan Fikri; Rani Setiawaty (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to develop and evaluate the feasibility of PEMAPOSI (Pemahaman Eksposisi), an interactive digital learning media designed to improve fourth-grade students’ comprehension of exposition texts. The study employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The media was developed in the form of an interactive flipbook integrating local cultural elements and was implemented in an elementary school setting. Data were collected through validation sheets and questionnaires involving media experts, material experts, teachers, and students. The results showed that PEMAPOSI obtained a validity score of 93.5% from media experts and 89.5% from material experts, both categorized as “very valid.” User response results also indicated a high level of practicality, with teacher and student assessments reaching 91.6% and 87.5% respectively. These findings indicate that PEMAPOSI is feasible, practical, and effective as a learning medium to support students’ understanding of exposition texts in elementary schools. The integration of interactive features and local cultural elements contributes positively to student engagement and learning outcomes.